TUGAS BADAN PENGAWASAN OBAT DAN MAKANAN TERHADAP DISTRIBUSI SUPLEMEN FITNES KOTA PEKANBARU TAHUN 2014 - SAPUTRA, BAYU TEGUH; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research is a study that examines the tasks food and drug control agency for the distribution of gym supplements pekanbaru city in 2013 This study used a qualitative method which is defined as the process of solving the problem was investigated by describing the state of the subject and object of research based on the facts that seem or how their This study concluded that the Oversight circulation fitness supplements by Hall of the Food and Drug Administration Pekanbaru based indicators, such as food standards, assessment act, and perform corrective action is still not performing optimally.Factors that affect the circulation supervision of fitness supplements by Hall of the Food and Drug Administration. Pekanbaru city are: the intensity of supervision where staff are indeed limitations need to be addressed government and sisters who are still less effective supervision, such as less strict control by the relevant agencies. So that the public can be protected from supplement products fitnessyang risk to consumer health.Key words : TASK, SUPERVISION, DISTRIBUTION SUPPLEMENTS GYM